2017
DOI: 10.1186/s12877-017-0613-2
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of prototype footwear and insoles to optimise balance and gait in older people

Abstract: BackgroundFootwear has the potential to influence balance in either a detrimental or beneficial manner, and is therefore an important consideration in relation to falls prevention. The objective of this study was to evaluate balance ability and gait patterns in older women while wearing prototype footwear and insoles designed to improve balance.MethodsOlder women (n = 30) aged 65 – 83 years (mean 74.4, SD 5.6) performed a series of laboratory tests of balance ability (postural sway on a foam rubber mat, limits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 39 publications
4
28
0
Order By: Relevance
“…Similar results were previously obtained when comparing classical slippers to a pair combining a set of key criteria to improve balance (rigid soles, closed heels, easy tightening). Despite the different shoe characteristics, only a walk test made it possible to differentiate the two shoe types [21].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were previously obtained when comparing classical slippers to a pair combining a set of key criteria to improve balance (rigid soles, closed heels, easy tightening). Despite the different shoe characteristics, only a walk test made it possible to differentiate the two shoe types [21].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding dynamic balance, Paton et al [17] found no differences in dynamic balance using different insoles. Other research found no negative effects of insoles or small positive effects of different types of insoles on dynamic balance [35,36]. A reason for the difference between static and dynamic balance might be the sensory input during dynamic activities.…”
Section: Insolesmentioning
confidence: 95%
“…Vibrating insoles might be used in combination with offloading devices that lead to decreased balance, in such a way that patients have the offloading benefits of the offloading devices without compromising balance. In other recent research prototype footwear and insoles were developed to optimize gait in older adults [36]. The footwear consisted of a firm rubber sole (25 mm thick under heel and 18 mm under the forefoot), a high collar to support the ankle, a firm heel counter, a ten degree bevel in the heel, and a slip resisting outsole.…”
Section: Other Solutionsmentioning
confidence: 99%
“…Athletic shoes are associated with decreased fall risk [20]. Shoes with a firm sole and enclosed heel optimise balance and gait compared with slippers [27].…”
Section: Morphological Changes With Ageingmentioning
confidence: 99%
“…Step width when doing a tandem walk was significantly narrower in shoes with textured insoles [27]. Balance improved with flat and textured insoles [52].…”
Section: Insolesmentioning
confidence: 99%